Performance improvement of an AVR system by symbiotic organism search algorithm-based PID-F controller - Ozgenc, Busra; Ayas, Mustafa Sinasi; Altas, Ismail Hakki (Neural computing & applications, 2022)
The automatic voltage regulator (AVR) system is commonly used in power systems to remain terminal voltage of generator at a specified level. The terminal voltage level is controlled by utilizing various controllers in an AVR system. Researchers aim to enhance dynamic performance of the AVR system besides minimize steady state error by employing various controllers in their studies. In most of these studies, evolutionary algorithms are used during controller design process. Evolutionary algorithms are commonly utilized to optimally tune controller parameters according to predefined objective function. In this study, a proportional-integral-derivative (PID) controller with filter (PID-F) is proposed for an AVR system in order to improve its dynamic performance. The proposed PID-F controller has four independent variables which are optimally tuned by utilizing symbiotic organism search (SOS) algorithm. In order to analyze the performance of the designed PID-F controller, step response of the AVR system is obtained and transient response analysis is performed. The obtained transient response characteristics are compared with available current studies proposing optimally tuned PID controllers for the AVR system. In addition, stability of the AVR system with the proposed SOS algorithm-based PID-F controller is analyzed by carrying out pole/zero map analysis and bode diagram analysis. Lastly, robustness of the proposed controller toward parameter uncertainties in the AVR system is examined. The results indicate that the proposed SOS algorithm-based PID-F controller enhances the transient response characteristics, stability and robustness of the AVR system and can be successfully employed in the AVR system.